A importância da filosofia na gênese da teologia cristã: uma reflexão sobre fé e razão em Joseph Ratzinger (1927–2022) - Oliveira, Gustavo Rohte de (2023)
This research focuses on the central theme of the importance of Philosophy in the genesis of Christian Theology, reflecting on faith and reason in the thought of Joseph Aloisius Ratzinger (1927 - 2022). Since the author attributes special value to Philosophy and the pursuit of reason within Christian Theology, a philosophical reflection on the topic is sought. Thus, the general objective of this research is to investigate the importance of philosophy in the process of 'theologizing' faith in Joseph Ratzinger. This endeavor unfolds into several specific objectives: 1) present an overview of the emergence of philosophy in opposition to Greek myths and its culmination in Christian Philosophy; 2) investigate Christian Theology as a constituted science and its relationship with Faith and Revelation; 3) demonstrate that Theology is, above all, an ontological study about God; 4) relate Philosophy and Christian Theology. The research, which is primarily bibliographic in nature, will be conducted through the method of interpretation, analysis, and investigation based on Joseph Ratzinger's writings on the proposed topic, focusing on his main works and some texts by commentators that address the rational claim of Theology. The central hypothesis of the research is that Ratzinger establishes a relationship between Philosophy and Theology, both in its genesis and in its methodological root. Researching the philosophical foundations of Theology in the third millennium is to perceive the importance of Religion in the formation of Western knowledge and a commendable initiative for dialogue between worlds that are simultaneously distant and close. Joseph Ratzinger argues that Christianity should have a natural and therefore philosophical foundation, thereby excluding the possibility of the Christian religion being based on myths. By being based on natural (rational) theology, it also becomes a richness for humanity.